Outdoor air pollution and psychiatric symptoms in adolescents: a study of peripheral inflammatory marker associations - Zundel, Clara G.; Shampine, MacKenna M.; Jakubiec, Alexander; Lewis, Christine; Brokamp, Cole; Strawn, Jeffrey R.; Jovanovic, Tanja; Ryan, Patrick H.; Woodcock, Eric; Yang, Zhao; Petriello, Michael; Marusak, Hilary (Frontiers in Psychiatry, 2025)
IntroductionFine particulate matter (PM2.5) air pollution is associated with increased internalizing symptoms (e.g. depressive and anxiety symptoms), particularly during adolescence—a critical period for the emergence of anxiety disorders and vulnerability to neurotoxicants. Preclinical studies suggest that inflammation, including cytokines, reactive proteins, and lipid mediators, may explain the link between PM2.5 and psychiatric risk. However, growing evidence suggests that these relationships may differ by sex, with females potentially more vulnerable to the effects of air pollution on psychiatric symptoms, though the underlying mechanisms remain unclear.MethodsThis study examined the relationships among recent (past-month) PM2.5 exposure, peripheral inflammatory markers, and anxiety and depressive symptoms in 78 adolescents (M ± SD = 13.3 ± 2.3 years, 48.7% female) from the Detroit, MI area.ResultsHigher PM2.5 concentrations were significantly associated with elevated levels of inflammatory lipid mediators: PGE2, 12(S)-HETE, 12(S)-HEPE, and 15(S)-HETE. A significant PM2.5-by-sex interaction was observed for IL-6, with higher PM2.5 exposure associated with higher IL-6 concentrations in females but not males. Additionally, higher PM2.5 concentrations were significantly associated with greater total anxiety, generalized anxiety, and social anxiety symptoms, but only in females. Higher IL-8 concentrations were associated with greater depressive symptoms, and a significant TNF-α-by-sex interaction was observed for total and social anxiety symptoms, with higher TNF-α concentrations linked to greater symptoms in females but not males.DiscussionThese findings suggest that PM2.5 exposure is associated with inflammation and anxiety symptoms in adolescence, with notable sex differences. As a modifiable risk factor, reducing outdoor air pollution exposure may help mitigate psychiatric symptoms in youth.